Topography of Shrines of Bukhara in the Work of “Toohfat Uz-Zoirin” - Jurayeva Nafisa Olimovna; Mahmmoud Hussein Al Rahman (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
In the following article the role of the topography of cemeteries in the formation of the architectural appearance of the Bukhara city as it appears in the treatise of the “Toohfat uz-zoirin” and the issue of importance of the contemporary topographical significance of these cemeteries mentioned in the treatise.